Memacu Pemakaian Bahan Bakar Gas - Ibrahim, Irwan (Warta Penelitian Perhubungan, 2011)
Soaring oil price due to political upheaval in middle east becomes worldwide issue. Tiierefore developing countries try to exploit and make use of their natural gas and reduce import of oil. Usage of natural gas in the form of compressed natural gas (CNG) for transportation is the top priorihj in densed populated cities. TI1e objective is not only to diversify energy use but more important is to improve air quality. Indonesia started to introduce CNG in Jakarta in 1986. Unfortunately this introduction did not continue. CNG retums to the market when Jakarta launched its Bus Rapid Transit namely Trans Jakarta with CNG bus fleet in 2004. Local government of Jakarta wishes to encourage taxis, other public transport, and private cars in Jakarta to use CNG. But the response is not good, public interest on CNG is still low. TI1is paper tries to assess the main reason of sluggish progress of CNG program in Jakarta, taking Delhi case as the bench mark for the improvement. As the same problem also happened in other big cities, CNG program in Surabaya, Pelembang are discussed as well.Keywords : CNG, CNG filling station, converter kit, regulation enforcement